Telecentros como instrumento de inclusão digital: perspectiva comparada em Minas Gerais - Mauro Araujo Camara (2005)
This dissertation aimed to evaluate the TeleCenter as a technological tool for the process of digital inclusion. Based on the theoretical frame of Information Science, which try to understand the flows and consequences of information use in diverse fields, the conception of informational appropriation to understanding the different levels elaborated for the users, and the use of free software was overcome in this study as support for TeleCenter´s installation and expansion. The analysis searched to identify the vision of insertion of the programs, as well as the way of its establish and planning, its contents and results. The research was based on a comparative case study in two digital inclusion programs: an urban one, the Internet Cidadã, kept for the public power, under coordination of the Municipal City Hall of BeloHorizonte and a rural one, established for the not governmental organization Gemas da Terra. It had been visited two TeleCenters in Belo Horizonte and four in the rural area, in the districts of São Gonçalo do Rio das Pedras, Milho Verde, Tombadouro and Rodeador; interviewed the coordinators of the respective programs, four managers and 44 users. The results indicated that the managers supported the actions of the TeleCenters doing all the efforts for its effective functioning. In theurban area the users used the TeleCenters as source of leisure, school research and search of work and income, while in the rural area the TeleCenters was used for community mobilization, search of local development and to strength social relations in the communities. Some negative aspects were the high demand and low quality of hardware in the urban case and few amount of computers in the rural case. Thisdissertation concluded that TeleCenters is a basic tool to promote digital inclusion, that must be stimulated based on free software to ensure for all community to gain access to the technological tools and skills needed in the new world.